2014
DOI: 10.3390/ijms15046286
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Citicoline in in Vitro Models of Retinal Neurodegeneration

Abstract: In recent years, citicoline has been the object of remarkable interest as a possible neuroprotectant. The aim of this study was to investigate if citicoline affected cell survival in primary retinal cultures and if it exerted neuroprotective activity in conditions modeling retinal neurodegeneration. Primary retinal cultures, obtained from rat embryos, were first treated with increasing concentrations of citicoline (up to 1000 μM) and analyzed in terms of apoptosis and caspase activation and characterized by im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 31 publications
(30 reference statements)
1
36
0
4
Order By: Relevance
“…It is also thought to play a role in increasing the metabolism of cerebral structures via facilitating the biosynthesis of phospholipids in neuronal membranes [54], and inhibiting phospholipid degradation [53]. In vitro studies have previously reported data supporting Citicoline's protective effects against apoptosis, and reducing synaptic loss in retinal cell cultures [55,56]. Due to these features, Citicoline has been shown to have a neuroprotective effect in conditions such as stroke [57,58] and PD [59].…”
Section: Citicolinementioning
confidence: 99%
“…It is also thought to play a role in increasing the metabolism of cerebral structures via facilitating the biosynthesis of phospholipids in neuronal membranes [54], and inhibiting phospholipid degradation [53]. In vitro studies have previously reported data supporting Citicoline's protective effects against apoptosis, and reducing synaptic loss in retinal cell cultures [55,56]. Due to these features, Citicoline has been shown to have a neuroprotective effect in conditions such as stroke [57,58] and PD [59].…”
Section: Citicolinementioning
confidence: 99%
“…Specifically, in rodent retinal cultures and animal models of glaucoma, citicoline induced antiapoptotic effects in mitochondrial-dependent cell death, increased retinal levels of dopamine, counteracted retinal nerve fibers layer thinning, and promoted neurite regeneration (reviewed in Parisi et al, 2018 [52]). Furthermore, in vitro studies in retinal cells suggest that citicoline might have neuroprotective activity by blocking the excitotoxicity cascade leading to glutamate-mediated cell death [74,75] and decreasing both proapoptotic effects and synapse loss [76].…”
Section: Experimental Evidencementioning
confidence: 99%
“…Як відомо, він сприяє синтезу нуклеїнових кислот, білків, аце-тилхоліну та інших нейротрансміттерів, а також зменшує утворення вільних радикалів та гальмує вивільнення вільних жирних кислот. Завдяки цим властивостям цитиколін може одночасно гальму-вати різні ланки ішемічного каскаду, а також сприяти відновленню синаптичної передачі та збільшенню нейропластичності [9]. Висновок Отримані нами результати свідчать про по-зитивний вплив цитиколіну на шар ретинальних нервових волокон при виконанні лазеркоагуляції сітківки, що дозволяє рекомендувати його як ме-дикаментозний супровід панретинальної лазерко-агуляції у хворих на цукровий діабет 2-го типу.…”
Section: буковинський медичний вісникunclassified